Developing thinking skills in teaching of English as a second/foreign language at primary school - Tahsildar Tehrani, Seyed Hesameddin; Mohamed Razali, Abu Bakar (Human Resource Management Academic Research Society, 2018)
Developing skillful thinking contribute to young language learners’ language skills (Goh & Taib, 2006) and is a fundamental goal in educating school children in general (Hu et al., 2011) and in teaching English to young learners in particular (G. Ellis & Brewster, 2014). Fostering thinking skills develops school children’s cognitive abilities and leads to positive curricular outcomes (Higgins, Hall, Baumfield, & Moseley, 2005). However, despite the role of thinking skills in second language learning and teachers’ interest in thinking skills at the level of primary school (Alwadai, 2014; Gashan, 2015), the practice of teaching thinking skills at primary school is still lacking (Anyachebelu, 2012; Polat, 2015; Rodrigues, 2006). There is only modest contribution of the teachers’ practices to teaching thinking skills (Sardare & Saad, 2013) and there is a dire need for further work on primary students’ synthesis, analysis, and interpretation skills (Pilten, 2010). In addition, teachers of English language require practical ideas to improve students’ thinking skills (Adams, 2013) especially in the ESL/EFL contexts. Through a rigorous review of previous research on fostering thinking skills and provides a series of strategies or techniques, namely Content-Based Instruction, Task-Based Language Teaching Approach, English Literature, and Mental Modelling in Reading Comprehension, the authors argue that these strategies or techniques can be used for teaching or embedding thinking skills in the context of English as a Second/Foreign Language for young learners at primary school.